Fully integrated care for frail elderly: two American models - Dennis L. Kodner; Corinne Kay Kyriacou (International Journal of Integrated Care, 2000)
Purpose: Integrated care for the frail elderly and other populations with complex, chronic, disabling conditions has taken centre stage among policymakers, planners and providers in the United States and other countries. There is a growing belief that integrated care strategies offer the potential to improve service co-ordination, quality outcomes, and efficiency. Therefore, it is critical to have a conceptual understanding of the meaning of integrated care and its various organisational models, as well as practical examples of how such models work. This article examines so-called “fully integrated” models of care in detail, concentrating on two major, well-established American programs, the social health maintenance organisation and the program of all-inclusive care for the elderly. Theory: A major challenge to understanding the performance and outcomes of fully integrated care and other organisational models is the lack of a meaningful, analytical paradigm. This article builds upon the work of Walter Leutz, to develop a framework by which new and existing programs can be analysed. This framework is then applied to the two American models that are the focus of this article. Methods: Existing data about integrated care in general, and the two model programs in particular, were collected and analysed from reports published by governmental and non-governmental organisations, and journal articles retrieved from Medline, HealthStar and other sources. Results and conclusions: This analysis strongly suggests that fully integrated models of care, such as the social health maintenance organisation and program of all-inclusive care for the elderly, are not only feasible, but offer significant potential to improve the delivery of health and social care for frail elderly patients. In addition, the authors identify the factors that are the most critical to the success of fully integrated care, and offer lessons for their development and implementation. Finally, issues are raised concerning the transferability of this complex model to other countries, as well as the vital importance of evidence-based evaluation research in furthering the evolution of integrated care.